The Higher Your Implicit Affiliation‐Intimacy Motive, the More Loneliness Can Turn You Into a Social Cynic: A Cross‐Cultural Study. Issue 2 (21st November 2015) - Hofer, Jan; Busch, Holger; Raihala, Carolin; Poláčková Šolcová, Iva; Tavel, Peter
Abstract: Research has shown that the strength of the implicit affiliation‐intimacy motive moderates the effects of satisfaction and frustration of the need for affiliation‐intimacy: Low relatedness was more closely related to envy for people high in the implicit affiliation‐intimacy motive. The present study tests a moderating effect of the strength of the implicit affiliation‐intimacy motive on the association between low relatedness and social cynicism in samples of elderly people from Germany, the Czech Republic, and Cameroon. A total of 616 participants provided information on their implicit affiliation‐intimacy motive, relatedness, and social cynicism. As hypothesized, a moderation effect of the strength of the implicit affiliation‐intimacy motive was found that held true regardless of participants' culture of origin: For people high in the implicit affiliation‐intimacy motive, a lack of relatedness was associated with higher levels of social cynicism. Our findings complement other theories stating that positive relationships with others are a significant part of successful aging.